Effects of ambient temperature on growth performance, slaughter traits, meat quality and serum antioxidant function in Pekin duck - Xu, Congcong; Sun, Dongyue; Liu, Yi; Pan, Ziyi; Dai, Zichun; Chen, Fang; Guo, Rihong; Chen, Rong; Shi, Zhendan; Ying, Shijia (Frontiers in Veterinary Science, 2024)
The present study investigated the effects of temperature on growth performance, slaughtering traits, meat quality and antioxidant function of Pekin ducks from 21-42d of age. Single factor analysis of variance was used in this experiment, 144 21d-old Pekin ducks were randomly allotted to 4 environmentally controlled chambers: T20(20 °C), T23(23 °C), T26(26 °C) and T29(29 °C), with 3 replicates in each group (12 ducks in each replicate), the relative humidity of all groups is 74%. During the 21-day trial period, feed and water were freely available. At 42d, the BW (body weight) and ADG (average daily gain) of T26 were significantly lower than T20 (p < 0.05), and the T29 was significantly lower than T20 and T23 (p < 0.05). The ADFI (average daily feed intake) of T26 and T29 were significantly lower than T20 and T23 (p < 0.05). Compared to the T29, the T20 showed a significant increase oblique body length and chest width, and both the keel length and thigh muscle weight significantly increased in both the T20 and T23, while the pectoral muscle weight increased significantly in other groups (p < 0.05). The cooking loss of the T29 was the lowest (p < 0.05). The T-AOC (total antioxidant capacity) of T29 was significantly higher than the other groups (p < 0.05), the SOD (superoxide dismutase) in the T29 was significantly higher than the T23 and T26 (p < 0.05). In conditions of 74% relative humidity, the BW and ADFI of Pekin ducks significantly decrease when the environmental temperature exceeds 26°C, and the development of body size and muscle weight follows this pattern. The growth development and serum redox state of Pekin ducks are more ideal and stable at temperatures of 20°C and 23°C.